2018
DOI: 10.1016/j.omtn.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of MALAT1, GAS5, SRA, and NEAT1 lncRNAs in Breast Cancer Tissues from Young Women and Women over 45 Years of Age

Abstract: Breast cancer, as the most common cancer in women worldwide, represents about 30% of all cancers affecting women. Long non-coding RNAs (lncRNAs) have been implicated in the regulation of several biological processes, and their dysregulation in cancer has well been documented. To investigate possible age-dependent variations in expression profiles of lncRNAs, we evaluated the expression levels of four lncRNAs, i.e., MALAT1, GAS5, SRA, and NEAT1, in breast cancer (BC) samples obtained from younger (<45 years) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 36 publications
3
52
1
1
Order By: Relevance
“…Along with miR-204, the levels of NEAT1 differed between HER2-positive status and the other respective status. A significant upregulation of NEAT1 was observed in tumor tissues of BC patients by several previous studies (Arshi et al, 2018;Choudhry et al, 2015;Li et al, 2017b;Zhang et al, 2017b;Zhao et al, 2017). Similar to our findings, Zhang et al (2017b) observed that high expression of NEAT1 in BC tissues was closely related to lymph node metastasis and stimulated cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…Along with miR-204, the levels of NEAT1 differed between HER2-positive status and the other respective status. A significant upregulation of NEAT1 was observed in tumor tissues of BC patients by several previous studies (Arshi et al, 2018;Choudhry et al, 2015;Li et al, 2017b;Zhang et al, 2017b;Zhao et al, 2017). Similar to our findings, Zhang et al (2017b) observed that high expression of NEAT1 in BC tissues was closely related to lymph node metastasis and stimulated cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…54 GAS5 levels were significantly decreased in BC tissues than those in adjacent normal breast epithelial tissues. 18,55,56 One study showed low GAS5 expression in triple-negative breast cancer (TNBC) tissues than that of adjacent non-tumor tissues, and was associated with clinical stage, lymph node metastasis (LNM) and OS. 19 Decreased expression of GAS5 was found in BC tissues and was negatively associated with later TNM stage and shorter OS time as well.…”
Section: Clinical Relevancementioning
confidence: 99%
“…45 Intriguingly, BC patients aged less than 45 years old who had much lower GAS5 levels than those of old cases showed the poorer prognosis. 56 Others found that GAS5 levels were decreased frequently in estrogen receptor-negative (ER-) BC tissues and cells, and were related with large tumor size, advanced TNM stage. 57 BC patients with low GAS5 levels in plasma and a high Ki67 proliferation index before surgery were positively associated with LNM after surgery, indicating that plasma GAS5 may have the potential to assess the surgical effects and prognosis for patients with BC.…”
Section: Clinical Relevancementioning
confidence: 99%
“…This highlights that the novel lncRNA RP11-48B3.4 may via interacting with some encoding genes by different mechanisms involved in pathogenesis of the IDC. There is evidence that lncRNAs through in uencing expression of other coding and non-coding genes play key roles in development of BC [27]. In this way, one suggested mechanism is competing endogenous RNA (ceRNA) function through which lncRNAs via sponging miRNAs regulate expression of mRNAs in regulatory molecular networks whose roles in cancer development, especially in BC, are emerging with clinical signi cance [28,29].…”
Section: Discussionmentioning
confidence: 99%